2023
DOI: 10.1177/20563051231182359
|View full text |Cite
|
Sign up to set email alerts
|

The Thermometer Broke! Digital Purdah, Class, and Gender Transgressions on Pakistani TikTok

Abstract: Research on women’s social media practices in Muslim societies has primarily focused on middle-class or elite women, such as influencers, activists, and members of online communities. However, we know little about working-class women’s use of social media in Muslim contexts. Using ethnography and interviews, I analyze TikTok’s early popularity with working-class women in Pakistan and report three main findings. First, TikTok’s initial reception in Pakistan was fractured across class lines; whereas middle-class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For example, in a study conducted by Siles et al (2022), it was observed that participants attributed political valences to TikTok recommendations, specifically linking them to a presidential candidate from Costa Rica based on the interests of users “with the same profile” (p. 12). Another example is Kamran’s (2023) recent study on Pakistani TikTok users, where the author observes that the presence on TikTok is often associated with a “low-class femininity” (p. 1) in Pakistani society. Algorithms play a significant role in how users search for information and, simultaneously, in how knowledge systems are embodied through algorithms (Gillespie, 2014).…”
Section: Imaginaries and Stories Related To Tiktok’s Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study conducted by Siles et al (2022), it was observed that participants attributed political valences to TikTok recommendations, specifically linking them to a presidential candidate from Costa Rica based on the interests of users “with the same profile” (p. 12). Another example is Kamran’s (2023) recent study on Pakistani TikTok users, where the author observes that the presence on TikTok is often associated with a “low-class femininity” (p. 1) in Pakistani society. Algorithms play a significant role in how users search for information and, simultaneously, in how knowledge systems are embodied through algorithms (Gillespie, 2014).…”
Section: Imaginaries and Stories Related To Tiktok’s Algorithmmentioning
confidence: 99%
“…However, this restricted scope can be advantageous as it validates the institutional elements unique to Romania. Further studies could investigate the complex interplay between the algorithmic stories and the institutional values in other cultural contexts, given the fact that research has been carried out on TikTok activity in Costa Rica (Siles et al, 2022), Pakistan (Kamran, 2023), and so on. Another limitation arises from the relatively short distance between the stages of this study.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%